Conteúdos étnicos-raciais e ensino de arte na rede municipal de Uberlândia - Nascimento, Camila Ribeiro do (2018)
Realized in the guidelines of educational process, learning and creations in Arts, this essay aim to investigate how Visual Arts teacher's who works in the basic education of Uberlândia's city have been elaborating pedagogical practices related to the ethnic-racial field required in the art's teaching since the implementation of the Law 10.639/03. The main purpose of this study is to answer: How visual arts's teachers have been applying the ethnical and racial subjects in the basic education? Along with the following questions: 1.1- How do the arts's teachers interprets the Law 10.639 /03, as well as the social, the educational and the formative demands in the educational work of ethnic-racial contents in basic education? And 1.2 — How arts's teachers have developed the educational projet in the definition of themes, contents, theoretical, artistic and methodological references of the ethnic-racial's content teaching in basic education? The course of this research comprised bibliographical, documentary and field analysis through a qualitative approach. The field of research involved two phases: the first one through the application of a person-to-person interview through objectives questions, and the second, when the semi-structured interviews were conducted, which led to the multiple case study. The analyzed data allowed us to think about the reflexive practices that teachers and students have been building together, aiming at an education without discrimination and prejudice in the daily life at school. On the other hand, it was realized that it is necessary to broaden our understanding of this subject, as there are still weaknesses in the development of pedagogical practices that results in works with many stereotypes. Despite of all efforts, as we have seen in the bibliographical research, we are generally from a generation that learned that the focus of black history was linked only to slavery and that they were dominated by the white elite, which brought to the promotion of equality and the enhancement of cultural diversity. Therefore, it was concluded that teachers faces, in the daily life at school, the challenge of proposing activities that go out of common-sense and that do not emphasize only the célébration of the Black Consciousness, and in this way, it can promote a truly education for an effective inclusion of ethnic-racial relations in the school environment.